If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 1y = 3.85 Solving 3x + 1y = 3.85 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 3x + 1y + -1y = 3.85 + -1y Combine like terms: 1y + -1y = 0 3x + 0 = 3.85 + -1y 3x = 3.85 + -1y Divide each side by '3'. x = 1.283333333 + -0.3333333333y Simplifying x = 1.283333333 + -0.3333333333y
| 12n=162 | | (5a-3b)+(2a+6b)= | | x(x-6)=x^2+5x+4 | | Y+23=111 | | 2(t-4)+6t=4(2t+3)-9 | | 4x-3+73=90 | | 4s-10=8-2s | | X-24=53 | | 4ln(5x+4)=22 | | g(3y)x-2x^2= | | 3(2c+1)=2(4c-1) | | 7n=219 | | 15d=3d | | (m-1)x^2-2mx-m-4=0 | | 15=9x-1 | | 7(6)+4+7(6)+4-4+(7(6)+4)=180 | | 1500mL=L | | f(2x-1)=8x^2-2x | | 360*17/24 | | 5.5+7= | | X-0.2=100 | | 3m-1=2m-6 | | 30=10+.75x | | 4x^4+184x=10 | | 10x+20*47-20x=640 | | 8+2(4w-3)=-2(7w-5)+6w | | 10n-7=-13 | | 8x-1=89 | | 10(7.5)=2(7.5)+60 | | 19x-5=11x-45 | | 5x=6-4x^2 | | x-5+x=2x-4 |